Desarrollo de mejor tecnologia para sistemas de produccion de yuca dentro del contexto de proyectos integrados - Moreno, R.A. (International Center for Tropical Agriculture, 1991)
The need to conduct research on agricultural systems is emphasized since the understanding of traditional systems facilitates technology development. In the case of cassava production systems, technology development makes technical recommendations available that, upon being applied to systems currently used by farmers, allow improved production conditions by increasing the quantity of product obtained per unit of limiting resource used. In the case of small farmers, it is necessary to consider carefully that any technological innovation is in itself a social-type product. Recently, the development of technology on farmers' holdings, with the greatest possible participation of farmers in the whole process of development, will partly prevent inefficient technology transfer. Technology is normally developed for the purpose of modifying yield, which is considered a function of environment and management. Components of the environment may be considered as parameters (characters unmodifiable by man) or as variables (soil fertility, natural enemies, weeds, etc.). Management is the body of decisions, and their consequent actions carried out by man so that a species or a group of species will transform the resources of a given environment into products of value to satisfy a need. Methodological considerations for developing better technology involve (1) the description of production system, the physical-biological environment and farmers; (2) the design of improved production options; (3) field testing of improved options with farmers; and (4) validation of the best technological options with a larger number of farmers and elaboration of production and transfer plans. The function of technical recommendations is discussed as well as pre-production tests. (CIAT)